PERANCANGAN SISTEM PENGOLAHAN DATA JEMAAT BERBASIS WEB PADA GEREJA GKPI KOTA JAMBI - Sagala, Dame Christine; Sadikin, Ali; Irawan, Beni (JOURNAL V-TECH (VISION TECHNOLOGY), 2018)
The data processing systems is a very necessary way to manipulate a data into useful information. The system makes data storage, adding, changing, scheduling to reporting well integrated, so that it can help parts to exchange information and make decisions quickly. The problems faced by GKPI Pal Merah Jambi are currently still using Microsoft Office Word and in disseminating information such as worship schedules, church activities and other worship routines through paper and wall-based worship services. To print worship and report reports requires substantial operational funds, in addition to data collection and storage there are still deficiencies including recording data on the book, difficulty in processing large amounts of data and stored in only one special place that is passive. Based on the above problems, the author is interested in conducting research with the title Designing Data Processing Systems for Web-Based Churches in the GKPI Pal Merah Church in Jambi. The purpose of this study is to design and produce a data processing system for the church. Using this system can facilitate data processing in the GKPI Pal Merah Jambi Church. This study uses a waterfall development method, a method that provides a systematic and sequential approach to system needs analysis, design, implementation and unit testing, system testing and care. Applications built using the web with MySQL DBMS database, PHP programming language and Laravel.